The Early Generation of Qur’anic Exegetes in Indonesia: Intellectual Legacy, Interpretive Methodologies, and Socio Historical Context - Muhith Muhith (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
Studies on the history of Qur’anic exegesis in Indonesia have largely focused on modern figures, while the earliest generation of local exegetes remains insufficiently mapped in a systematic manner. Yet their works and interpretive approaches played a crucial role in transmitting Islamic scholarship and shaping indigenous intellectual traditions. This study aims to identify prominent early Indonesian mufassirs, examine their exegetical writings, and analyze their methodologies as well as the socio historical contexts that informed their interpretations. Employing a qualitative design with a historical-philological approach, the research is based on library study of early printed tafsirs, manuscript sources, and relevant secondary literature. Data were analyzed through thematic content analysis and comparative methodological examination. The findings indicate that early Indonesian exegetes were strongly influenced by Middle Eastern scholarly networks, while simultaneously articulating local elements through the use of Malay language, engagement with communal religious practices, and responses to colonial conditions and social change. The study concludes that early Nusantara tafsir represents a synthesis of global Islamic traditions and local realities, providing a foundational framework for the later development of Qur’anic studies in Indonesia.